Industrialization and Convergence of West Java Manufacturing Labor Productivity, Indonesia - Nasution, Nauli Fitriyanni; Wahyuni, Krismanti Tri (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
West Java as a national manufacturing center has experienced industrialization since 1989. This is marked by the continuous increase in the manufacturing sector so that it is able to shift other sectors. Unfortunately, the industrialization that occurred in West Java was not followed by a reduction in the manufacturing labor productivity in West Java. The convergence of manufacturing labor productivity in West Java is an important phenomenon because inequality can lead to a different pace of development and exacerbate inequality. This study uses dynamic panel data regression with the first-different GMM (FD-GMM) method for inferential analysis and Location Quotient (LQ), Klassen Typology and the calculation of the coefficient of variation for descriptive analysis. The results showed that only 7 out of 27 regencies/cities in West Java had the economy dominated by the manufacturing sector and there were fluctuations in the productivity of the manufacturing workforce in these areas. Based on Klassen's Typology, there are still many areas that are categorized as developing and underdeveloped areas. However, there is a decrease in inequality between regions as seen from the results of the convergence analysis. Sigma convergence and beta convergence occurred in West Java with the time needed to close half the gap (half-life convergence) of less than one year. Factors that significantly affect the convergence process of manufacturing labor productivity are the manufacturing labor productivity lag, FDI, DDI, and real wages of manufacturing workers.